"No High Like a Brownie High": A Content Analysis of Edible Marijuana Tweets. Issue 4 (May 2018) - Cavazos-Rehg, Patricia A.; Zewdie, Kidist; Krauss, Melissa J.; Sowles, Shaina J.
Purpose: To investigate tweets about marijuana edibles for surveillance into the content of edibles-related tweets among individuals socially networking about this topic on Twitter. Design: Cross-sectional analysis of tweets containing edible marijuana-related key words during 1 month. Setting: Twitter. Participants: Tweets sent during January 1 to 31, 2015. Methods: A random sample of 5000 tweets containing edibles-related key words was coded for sentiment (positive, negative, and neutral) by crowdsourced workers. Tweets normalizing or promoting edibles use were further analyzed, and demographic characteristics of the Twitter handles sending these tweets were inferred. Results: Of the 5000 tweets, 4166 (83%) were about marijuana edibles, and of those 75% (3134 of 4166) normalized or encouraged edibles use. Nearly half (48%, 1509 of 3134) of the tweets normalizing edibles mentioned wanting or planning to consume, currently consuming, or recently consuming edibles, and 12% (378 of 3134) described the intense or long-lasting effects following use. Individuals whose tweets promoted/encouraged edibles use were more likely to be young (between 17 and 24 years old) and of a racial/ethnic minority (52% black; 12% Hispanic) when compared to the Twitter average. Conclusion: Tweets that normalize edibles use have the potential to increase their popularity. The prevalence of tweets about edibles' intense high could have implications for tailoring prevention messages that could be important for youth and young adult minorities who were inferred to be disproportionately socially networking about edibles on Twitter.